Examining Values, Virtues, and Tradition in the Republic of Tuva with Free-List and Demographic Data - Purzycki, Benjamin G.; Bendixen, Theiss (The New Research of Tuva, 2020)
This article illustrates how using qualitative and quantitative social scientific methods together can help us examine sociocultural phenomena in precise, informative, and potentially useful ways. Using freely listed ethnographic data about what qualities Tuvans associate with “good” and “bad” Tuvan people, we examine general cultural patterns of Tuvan virtues. The data was collected in Tuva in 2009–2010 by interviewing nearly 100 Tuvans in Kyzyl and Western Tuva. We also explore within-group contrasts by applying standard modeling techniques to this ethnographic data, finding demographic associations with listing specific items and those items’ salience. We conclude with a discussion of the promise and limitations of these methods.